Anteprojeto arquitetônico de um templo cristão protestante contemporâneo - TEIXEIRA, Larissa Galvão (2023)
This undergraduate thesis in architecture and urbanism proposes an architectural project for a protestant church "Assembly of God" located in the Coqueiro on Belém of the Pará. Initially, the early history of Christianity and the treatment of Protestantism were studied to serve as the theoretical basis for the elaboration of the proposal. We also studied the concepts related to environmental comfort in the thermal, light and acoustic aspects, which are fundamental for the definition of the party and all project decisions. The emphasis on acoustic conditioning was the main strategy in the proposed elaboration given the importance and necessity of acoustic comfort in the Protestant churches. For this purpose, evangelical worship was heard in several evangelical churches in Belém and Ananindeua, in order to the reverberation time of the nave were calculated, sound insulation, room geometry and positioning of the sound reflecting mirrors. Finally, a published proposal contemplates all application parameters and uses a technically comfortable space.